Spectroscopic, electrochemical and X-ray crystallographic properties of a novel palladium(II) complex of thioamide deprotonated di-2-pyridyl ketone thiosemicarbazone (dpktsc-H)−. Issue 17 (2nd September 2017) - Bakir, Mohammed; Lawrence, Mark A. W.; Ferhat, Marhoun; Conry, Rebecca R.
Abstract: The reaction between di-2-pyridyl ketone thiosemicarbazone (dpktsc) and PdCl2 (CH3 CN)2, generated in situ from the reaction between PdCl2 and CH3 CN, gave the unprecedented [Pd2 Cl3 (κ 5 -Npy, Nim, S, Npy, Nam -dpktsc-H)]·2CH3 CN (1 ) complex (py = pyridine, im = imine and am = amide). The identity of1 was confirmed via its elemental analysis and spectroscopic properties. Infrared and 1 H-NMR spectra confirmed the coordination of (dpktsc-H) − to the palladium ions. The electronic absorption spectra measured in dmso and dmf and density functional theory (DFT) calculations revealed metal-to-ligand charge-transfer (MLCT), d–d and intra-ligand charge-transfer (ILCT) electronic transitions. X-ray structural analysis on a crystal of [Pd2 Cl3 (κ 5 -Npy, Nim, S, Npy, Nam -dpktsc-H)]·H2 O (2 ) grown from dmf solution of1 confirmed its formulation and showed the solid-state structure contains a web of molecules locked via a network of non-covalent interactions. Electrochemical measurements on1 in dmf revealed metal- and ligand-based redox processes. In contrast to the electrochemical decomposition of uncoordinated dpktsc, coordinated (dpktsc-H) − in1 does not undergo electrochemical decomposition. Electrochemical titrations of1 with p -toluenesulfonic acid monohydrate ( p -TSOH) revealed electro-catalytic proton reduction. Over-potential ( η ) of 180 mV for the H2 evolution was observed and is comparable to several molecular electro-catalysts for proton reduction. Controlled-potential electrolysis confirmed the electro-catalytic proton reduction by the Pd-complex. Electrochemical reactions of CO2 in the presence of1 exhibited a proton dependence, and metal- and ligand-based electrochemical reaction. Abstract :